Transition Metal Compounds Synthesis, Properties, and Application - Haider, Sajjad; Haider, Adnan (IntechOpen, 2021)
This book explores synthesis, structural changes, properties, and potential applications of transition metal (TM) compounds. Over three sections, chapters cover such topics as the synthesis of pentoxide vanadium (V2O5), the effect of TM compounds on structural, dielectric properties and high-temperature superconductors, and TM-doped nanocrystals (NCs).